Design of Quaternary Logic Carry Look-Ahead Adder - Lohrasb, Nosratollah (2009)
In today's state-of-the-art VLSI technology, binary number system has been the choice for designing digital subsystems. Although technology development has made down scaling of devices possible, which in turn has resulted in a remarkable increase in density and functionality of VLSI systems, there are also significant drawbacks associated to the conventional binary number based system implementations. As the number of devices in VLSI circuits increases to billion of transistors in a chip area of , interconnection between the active devices both on chip and outside of a chip becomes considerably complicated. In a typical VLSI chip, about 70 percent of the chip area is occupied by interconnections whereas just 10 percent of the chip area is devoted to the devices and the remaining 20 percent is used for insulation. mm2 In this situation, multiple valued logics have attracted a considerable attention of researchers as a solution to overcome the above mentioned problem. Since fewer digits are required to represent a number in higher radices than in the binary number system, multiple valued logic circuits have the potential to minimize the number of interconnections. This thesis presents voltage-mode quaternary (4-valued) logic carry lookahead adder design using Silicon-On-Insulator (SOI) MOSFETs. The choice of adder subsystem is made because addition operation is the most frequently used operation in a general purpose system and in application specific processors. Further more, the other operations like subtraction, multiplication and division are based on addition operation of the arithmetic unit. In this study, an efficient logic to realize 4-valued logic addition operation is proposed. The presented method is in conjunction with binary logic concepts and is easily developed for look-ahead logic. Following the proposed method has resulted in logic circuits with shorter gate depth and faster speed of operation as compared to what the other researchers have proposed. To meet the design requirements of the proposed low-voltage low-power circuits, multiple threshold voltage SOI MOSFETs are used. This choice is made because of their capability to operate at low power supply voltages and their ability to remain at the adjusted threshold voltages while presenting better subthreshold characteristics compared to the bulk MOSFETs. The proposed half and full adder blocks are divided into a few subblocks which could be considered as primitive gates. Transistor-Resistor Logic is used to implement each of them. Spice simulations have been performed on the proposed logic subblocks and their transient behaviors have been studied. Finally, the propagation delay, power consumption and overall performance of the proposed circuits are compared with other adder circuits proposed by other researchers. The presented adder circuits in this work have shown up to 58% reduction in critical propagation delay and 20% less power dissipation resulting in 64% reduction in power-delay product in comparison with other reported work. When compared to the binary logic carry look-ahead adder using the same technology (SOI), 54.39% improvement in power dissipation was achieved.